Elabela and Apelin actions in healthy and pathological pregnancies. (April 2019) - Eberlé, Delphine; Marousez, Lucie; Hanssens, Sandy; Knauf, Claude; Breton, Christophe; Deruelle, Philippe; Lesage, Jean
Highlights: Elabela/apelin are crucial for embryo cardiovascular system formation and early placental development. Elabela-deficient mice display all the features of preeclampsia (PE). Apelin acts in mid/late gestation to modulate fetal angiogenesis and energy homeostasis. Clinical studies do not support a role of elabela in PE development. Abstract: Pregnancy is a dynamic and precisely organized process during which one or more baby develops. Embryonic development relies on the formation of the placenta, allowing nutrient and oxygen exchange between the mother and the fetus. Dysfunction of placental formation lead to pregnancy disorders such as preeclampsia (PE) with serious deleterious consequences for fetal and maternal health. Identifying factors involved in fetoplacental homeostasis could inform better diagnostic and therapeutic strategies for these pathological pregnancies. Here, we summarize actions of elabela, apelin and their common receptor APJ in the fetoplacental unit. Studies indicate that elabela is crucial for embryo cardiovascular system formation and early placental development, while apelin acts in mid/late gestation to modulate fetal angiogenesis and energy homeostasis. Most of these findings, drawn from animal models, indicate a key role of elabela/apelin-APJ system in the fetoplacental unit. This review also provides an overview of clinical studies investigating elabela/apelin-APJ system in pathological complicated pregnancies such as PE and gestational diabetes mellitus (GDM). While elabela-deficient mice display all the features of PE, current clinical studies show no difference in circulating elabela levels between PE and control patients which does not support a role in PE development. Conversely, apelin levels are increased during PE, but the use of apelin as an early PE marker remains to be fully investigated.